LEMON – an Open Source C++ Graph Template Library - Dezső, Balázs; Jüttner, Alpár; Kovács, Péter (Electronic notes in theoretical computer science, 2011)
This paper introduces LEMON, a generic open source C++ library providing easy-to-use and efficient implementations of graph and network algorithms and related data structures. The basic design concepts, features, and performance of LEMON are compared with similar software packages, namely BGL (Boost Graph Library) and LEDA. LEMON turned out to be a viable alternative to these widely used libraries, and our benchmarks show that it typically outperforms them in efficiency.